THE EVALUATION OF TEACHING ACTIVITIES OF THE INSTRUCTORS RUNNING PRACTICE COURSES IN TERMS OF STUDENT PERSPECTIVES - Aylin ÇELEN (Fırat University, 2019)
The aim of this study is to evaluate the teaching activities of the instructors running teaching practice courses in terms of the students at Abant Izzet Baysal University, School of Physical Education and Sports. Survey model was used in this study. This study was conducted on 287 subjects and 5 teaching practice courses (basketball, volleyball, handball, swimming, and general gymnastics). The students involved in the study were given "The Questionnaire of the Evaluation of Instructors Running Teaching Practice Courses” which developed by researchers. The data was compared in terms of the variables: gender, department (Physical Education Teaching, Coaching Education and Sport Management), class, and teaching practice course. Analyzing the data, frequency (f), percentage (%), mean ( ), standard deviation (sd), independent samples t test, one-way analysis of variance and Tukey test were used. The level of significance was determined p